Financial inclusion and monetary policy in West Africa / Sa'ad Babatunde Akanbi ... [et al.] - Akanbi, Sa'ad Babatunde; Dauda, Ridwan Olamilekan; Yusuf, Hammed Agboola; Abdulrahman, Abdulganiyu Idris (Universiti Teknologi MARA Selangor, 2020)
The study investigated the impact of financial inclusion on the effectiveness of monetary policy in West Africa for the period 2005 to 2018. The study employed Granger panel non-causality test developed by Dumitrescu and Hurlin to determine the direction of causality between inflation (a proxy for monetary policy) and indicators of financial inclusion. The system GMM was also employed to investigate the impact of each indicator of financial inclusion on monetary policy. The results show that financial inclusion is a significant determinant of monetary policy. The study concludes that financial inclusion should be broadened to include a large number of economic agents in the rural areas and informal sector because a large volume of financial transactions takes place within this sector.